Lactate and Myocardiac Energy Metabolism - Dong, Shuohui; Qian, Linhui; Cheng, Zhiqiang; Chen, Chang; Wang, Kexin; Hu, Sanyuan; Zhang, Xiang; Wu, Tongzhi (Frontiers in Physiology, 2021)
The myocardium is capable of utilizing different energy substrates, which is referred to as “metabolic flexibility”. This process assures ATP production from fatty acids, glucose, lactate, amino acids, and ketones, in the face of varying metabolic contexts. In the normal physiological state, the oxidation of fatty acids contributes to approximately 60% of energy required, and the oxidation of other substrates provides the rest. The accumulation of lactate in ischemic and hypoxic tissues has traditionally be considered as a by-product, and of little utility. However, recent evidence suggests that lactate may represent an important fuel for the myocardium during exercise or myocadiac stress. This new paradigm drives increasing interest in understanding its role in cardiac metabolism under both physiological and pathological conditions. In recent years, blood lactate has been regarded as a signal of stress in cardiac disease, linking to prognosis in patients with myocardial ischemia or heart failure. In this review, we discuss the importance of lactate as an energy source and its relevance to the progression and management of heart diseases.